Analysis of the Implementation of Singapore's Flight Information Region (FIR) Policy in Controlling Airspace Over Indonesia's Riau and Natuna Islands - Palito Sitorus (Syntax Corporation Indonesia, 2025)
The airspace over the Riau and Natuna islands is still controlled by the Singapore Flight Information Region (FIR), this has an impact on the Indonesian state. The takeover of Singapore's FIR by Indonesia was finally carried out through an agreement between the Government of Indonesia and Singapore signed on January 25, 2022. In order for this takeover to be implemented properly and smoothly and provide benefits for Indonesia both in terms of sovereignty, safety and economy, concrete steps are needed. This research aims to analyze how the implementation of the Singapore FIR takeover policy policy is implemented from a public policy perspective. This research uses a qualitative method with data collection techniques through in-depth interviews with each stakeholder directly involved. The data validation used used a triangulation technique, where the research location was carried out at the Ministry of Transportation, the Indonesian Air Force, and AirNav Indonesia. In this study, it was found that the implementation of the Singapore FIR takeover policy after the signing of the agreement experienced quite complex dynamics. Initially, the policy of taking over the FIR had not been conveyed holistically and clearly to all personnel involved in it, including procedures, technical instructions, and work plans were still not available, so this became an inhibiting factor in its implementation. In terms of resources, budgets, and equipment, these three stakeholders are still relying on their respective institutions. Bureaucratic inefficiencies that include aspects of organizational structure, division of authority, relationships between organizational units and so on make this implementation less effective in achieving the policy objectives that have been set. This research is the first research conducted on government science, especially in the field of Public Policy, so this research is a novelty. Some of the things that need to be suggested are the need to form an adhock organization equipped with a legal umbrella, as well as the existence of a budget allocation to support all activities that will be carried out, so that the implementation is carried out properly in accordance with its objectives.